2016
DOI: 10.1080/01635581.2016.1142585
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Acrylamide and the Risk of Endometrial Cancer: An Italian Case-Control

Abstract: The role of dietary acrylamide on the risk of hormone-related, and specifically endometrial, cancers is debated. Epidemiological data are scanty. Thus, we examined the relation between acrylamide intake and endometrial cancer risk in a case-control study conducted between 1992 and 2006 in 3 Italian areas. Cases were 454 women with incident, histologically confirmed endometrial cancer. Controls were 908 age-matched women admitted to the same network of hospitals of cases for acute, non-neoplastic conditions. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…37 In contrast to these cohorts, the range of intake was narrower in the studies that showed no association. [38][39][40][41] In the Japanese participants, intake range of quartiles, as well as the average intake, was considerably smaller than in the other studies that showed a significant association.…”
contrasting
confidence: 65%
See 3 more Smart Citations
“…37 In contrast to these cohorts, the range of intake was narrower in the studies that showed no association. [38][39][40][41] In the Japanese participants, intake range of quartiles, as well as the average intake, was considerably smaller than in the other studies that showed a significant association.…”
contrasting
confidence: 65%
“…Likewise, the EPIC cohort, which included 10 European countries, also had a wide intake range: the lowest was 8.8 μg/day in Italy and the highest was 35.5 μg/day in Denmark . In contrast to these cohorts, the range of intake was narrower in the studies that showed no association . In the Japanese participants, intake range of quartiles, as well as the average intake, was considerably smaller than in the other studies that showed a significant association.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For the exposure categories reported in each study, we extracted the mean or median depending on which was available. If unavailable, we inputted in the model the midpoint of each category or, when the extreme boundaries for the highest and the lowest exposure category were not reported, we entered a value 20% higher or lower than the closest cutoff (28,29). For this analysis, we used restricted cubic splines with three knots at fixed percentiles (10th, 50th, and 90th) of exposure distribution using generalized least-squares regression model (24).…”
Section: Discussionmentioning
confidence: 99%